Quantitative Fraction Evaluation of Dermal Collagen and Elastic Fibres in the Skin Samples Obtained in Two Orientations from the Trunk Region - Naveen Kumar; Pramod Kumar; Satheesha Nayak Badagabettu; Keerthana Prasad; Ranjini Kudva; Coimbatore Vasudevarao Raghuveer (Dermatology Research and Practice)
Background. Histomorphic evaluation of dermal collagen and elastic fibres was analysed by image analysis technique. The quantification of dermal elements was performed in skin tissues, collected in horizontal and vertical directions from trunk region and discussed under the perspective of consequences of scar related complications. Materials and Method. Total number of 200 skin samples collected from 5 areas of trunk region were processed histologically and subjected to tissue-quant image analysis. Statistical analysis involving mean with SEM and paired t test by SPSS were employed to the percentage values obtained from image analysis. Result. Among the chosen 5 areas of trunk region, abdomen showed the statistically significant difference for both collagen and elastic content between horizontal and vertical orientations (P< 0.05), whereas upper back, presternal, and lateral chest areas showed significant difference (P< 0.05) only for collagen and groin only for elastic content. Conclusion. The differences in the distribution of dermal collagen and elastic fibres in 2 directions of the samples from the same areas might be attributed to final outcome of wound healing process by influencing the appearance and behaviour of scar related complications in the region of trunk.